Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00213-015-4026-7
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin-induced spiritual experiences and insightfulness are associated with synchronization of neuronal oscillations

Abstract: These results provide systematic evidence for the direct association of a specific spatiotemporal neuronal mechanism with spiritual experiences and enhanced insight into life and existence. The identified mechanism may constitute a pathway for modulating mental health, as spiritual experiences can promote sustained well-being and psychological resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
99
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 97 publications
22
99
2
2
Order By: Relevance
“…Scores of the spiritual experiences subscale of the 5D-ASC questionnaire were also associated with increased lagged phase synchronization of d oscillations between parahippocampal regions and the RSC. Kometer et al, (2015) speculate that the neuronal network processes they identified may constitute a crucial pathway that can be modulated by serotonergic receptors to regulate mental health, a conclusion that would be consistent with some of the potential positive mental health outcomes discussed earlier in this section.…”
Section: Psychedelics Can Engender Ecstatic States With Persistentsupporting
confidence: 75%
See 3 more Smart Citations
“…Scores of the spiritual experiences subscale of the 5D-ASC questionnaire were also associated with increased lagged phase synchronization of d oscillations between parahippocampal regions and the RSC. Kometer et al, (2015) speculate that the neuronal network processes they identified may constitute a crucial pathway that can be modulated by serotonergic receptors to regulate mental health, a conclusion that would be consistent with some of the potential positive mental health outcomes discussed earlier in this section.…”
Section: Psychedelics Can Engender Ecstatic States With Persistentsupporting
confidence: 75%
“…These findings of Kometer et al (2015) provide further evidence that decreased ongoing oscillations below 20 Hz, particularly u/a oscillations, may be a common mechanism of action of psychedelics. The decrease in lower frequency oscillations was found to be localized within an extended network that included the PCC, RSC, ACC, and parahippocampal regions, a network that strongly overlaps with the default mode network (DMN).…”
Section: Psychedelics Can Engender Ecstatic States With Persistentsupporting
confidence: 57%
See 2 more Smart Citations
“…Moreover, an especially strong relationship was found between PH-RSC decoupling and ego-dissolution (see also ref. 10). Thus, in the same way the neurobiology of psychedelicinduced visual hallucinations can inform on the neurobiology of visual processing, so the neurobiology of psychedelic-induced egodissolution can inform on the neurobiology of the "self" or "ego" (37), and the present results extend our understanding in this regard, implying that the preservation of DMN integrity, PH-RSC communication, and regular oscillatory rhythms within the PCC may be important for the maintenance of one's sense of self or ego.…”
Section: Discussionmentioning
confidence: 99%